Socio-Economic inequalities in accessing treatment of non-communicable diseases in Egypt using health issues survey 2015 - Elmoneer, Radwa Ahmed (AUC Knowledge Fountain, 2020)
The right to health is a fundamental human right, medications constitute a vital component of any health system worldwide. Hence, access to medicines is one entitlement of the right to health, and governments pay increasing concerns to improve equitable access to healthcare and medications among all citizens. Egypt is a middle income country, with tight resources and capabilities to spend on health, and a pluralistic and fragmented healthcare system. Therefore, aggravated challenges are facing the government towards the achievement of the "Health for all" constitutional right. Identifying where inequalities exist, and monitoring their change over time, is a major prerequisite towards creating an equity-oriented health sector. Therefore, Egypt Health Issues Survey from 2015 was used to assess the situation of equitable access to healthcare as represented in treating the Non Communicable Diseases, and to gauge the extent to which the different socio-economic determinants impact access to medications among NCD patients. Only 69.2% of the population of NCD patients in the age range (15-59 years) have a complete access to NCD treatment, while the other 30.8% have incomplete access to treatment. Irrespective of age, gender, place of residence, income, education, marital and employment status, private facilities were the provider of choice, for receiving NCD(s) care and treatment. Hence, NCD patients incur higher financial burden; the average out-of-pocket spending on treatment in a private health care facility is 3.5 times more than in a governmental healthcare facility. NCD treatment is an essential treatment that should be accessible for all patients irrespective of their age, sex, place of residence, economic status, etc. However, significant inequalities in accessing NCD treatment were detected among the different social groups, where complete access to NCD treatment is skewed against the poor, young-aged, males and those living outside Urban Governorates. Inequalities in the different socioeconomic factors impacted the inequality in accessing treatment with varying degrees; the main determinant is wealth, responsible for over 90% of the detected inequality; followed by education, age, and type of place of residence. Generally, policymakers should work on improving the overall population access to NCD treatment through improving medications availability and affordability at both private and governmental healthcare facilities, and special programs should target underprivileged groups. The results and inequality data generated from this research should provide a foundation for incorporating equity into evidence-based health planning, and also assessing whether current health initiatives promote equity in accessing treatment.